Biaxial testing of metal samples on testing machines with one load axis - K. A. Vansovich; V. I. Yadrov (Омский научный вестник)
The necessity of experimental studies to assess the growth rate of fatigue cracks under biaxial loading is substantiated. An overview of testing machines for biaxial testing of metal samples, devices and fixtures used to ensure biaxial loading is made. An original device for distributing the vertical force of the testing machine along two axes of a cruciform sample is described.